The combination effects of K2O and PbO poisoning on NH3-SCR TiO2-CeO2 catalyst. Issue 5 (October 2021) - Cao, Jun; Lu, Zhuquan; Teng, Liumei; Qiao, Xu; Liu, Weizao; Wu, Hongli; Jiang, Lijun; Wu, Qirong; Liu, Qingcai
Abstract: TiO2 -CeO2 catalyst is a promising material for removal of NO x by NH3 -SCR reaction. The poisonous substances existing in flue gas cause serious deactivation of the catalyst. However, most of the researches had focused on the effect of a single toxic component, while the actual flue gas contains multiple toxic components. In this work, the combination of K2 O and PbO poisoning effects on NH3 -SCR performance over the TiO2 -CeO2 catalyst were investigated. A stronger poisonousness was found when K2 O and PbO were simultaneously introduced. The characterization results showed that the coexistence of K2 O and PbO hinder the transfer of electrons between TiO2 and CeO2, and worsen the decrease of surface adsorbed oxygen, the relative ratio of Ce 3+, as well as the surface acidity. In situ DRIFTS results showed that the decrease of Brønsted acid caused by K and Pb was larger than Lewis acid. Additionally, the combination of K and Pb reduced the activation performance of NO x species. Finally, the TiO2 -CeO2 catalyst's Langmuir-Hinshelwood (L-H) mechanism did not change when K and Pb were introduced. Graphical Abstract: ga1 Highlights: The poisoning degree increased when K and Pb co-existed. K-Pb-Ti-Ce had fewer surface adsorbed oxygen and Ce 3+ . Weaker NH3 adsorption and NO x activation caused by K and Pb combination poisoning. K and Pb would not affect the reaction mechanism over Ti-Ce.